Optimization-Based Energy Management for Multi-energy Maritime Grids - Fang, Sidun; Wang, Hongdong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This open access book discusses the energy management for the multi-energy maritime grid, which is the local energy network installed in harbors, ports, ships, ferries, or vessels. The grid consists of generation, storage, and critical loads. It operates either in grid-connected or in islanding modes, under the constraints of both power system and transportation system. With full electrification, the future maritime grids, such as all-electric ships and seaport microgrids, will become (3z(Bmaritime multi-energy system(3y (Bwith the involvement of multiple energy, i.e., electrical power, fossil fuel, and heating/cooling power. With various practical cases, this book provides a cross-disciplinary view of the green and sustainable shipping via the energy management of maritime grids. In this book, the concepts and definitions of the multi-energy maritime grids are given after a comprehensive literature survey, and then the global and regional energy efficiency policies for the maritime transportation are illustrated. After that, it presents energy management methods under different scenarios for all-electric ships and electrified ports. At last, the future research roadmap are overviewed. The book is intended for graduate students, researchers, and professionals who are interested in the energy management of maritime transportation.s
Introduction to the Next-generation Maritime Grids -- Energy Efficiency Indexes for Maritime Grids -- Shipboard Energy Management under Uncertain Weather Conditions -- Shipboard Energy Management with Gas Capture Systems -- Shipboard Energy Management with Renewable Power Integration -- Multi-energy Management for Cruise Ships -- Multi-energy Management for Seaport Microgrids -- Maritime Applications of Energy Storages and Fuel Cells -- The Way Ahead.
Keywords: Offshore structures; Energy policy; Energy and state; Power electronics; Electric power distribution; Offshore Engineering; Energy Policy, Economics and Management; Power Electronics; Energy Grids and Networks